Socialization of Waste Management in the Community Environment in Talang Perapat Village - Jekzen, Beni; Paramita, Sita; Hidayat, Taofik; Marwanto, Marwanto; Ninosari, Devina; Gayatri, Ida Ayu Made Er Meytha; Soleh, Ahmad (Jurnal Pengabdian Mandiri, 2025)
The Community Service Program (KKN) is a form of student dedication to society aimed at applying the knowledge they have acquired in higher education to real-life situations. This study aims to describe the implementation of mutual cooperation (gotong royong) involving KKN students in the management and disposal of waste in Talang Perapat Village, Seluma Barat Sub-district, Seluma Regency. The method used in this study is descriptive qualitative, with data collected through observation, interviews, and documentation. The results show that the KKN activities—which include environmental cleanliness education, the construction of separate waste bins, training on yard utilization, recycling workshops, environmental campaigns, and the establishment of environmental cadres—had a positive impact on changing community behavior. Residents who were previously less concerned about cleanliness began to sort waste, maintain environmental hygiene, and actively participate in community-based clean-up efforts. This program also succeeded in reviving the spirit of mutual cooperation (gotong royong), which had faded due to rapid social changes. By involving all elements of the community, the KKN activities in Talang Perapat Village had a positive impact not only on physical environmental conditions but also on strengthening social values in community life.